Framework of next-generation internet security management:bright internet initiative - Xin TANG; Xiaosong WU; Wei HUANG; JaeKyu LEE; Xi ZHAO; Jiayin WANG (大数据)
The internet has become a minefield of crime,fakes,and terrors perpetuated by anonymous users on a global scale.In order to fundamentally solve the problem of cyber security,the Association for Information Systems (AIS) has developed a grand initiative for the bright internet based on information and communication technology and big data technology.The proposed initiative not only provides a new research framework for the traditional cyber security framework,but also protects user privacy at an appropriate level.Based on the five principles of bright internet and the data of Chinese cyber security,three approaches were proposed to achieve security architecture.